Glioblastoma-Specific Anticancer Activity of Pheophorbide a from the Edible Red Seaweed Grateloupia elliptica - Cho, MyoungLae; Park, Gab-Man; Kim, Su-Nam; Amna, Touseef; Lee, Seokjoon; Shin, Woon-Seob (KOREAN SOC MICROBIOLOGY & BIOTECHNOLOGY, 2014)
The chlorophyll-related compound pheophorbide a (Pa) was successively purified from an edible red seaweed, Grateloupia elliptica, using silica, octadecyl silica column chromatography and reversed phase-high-performance liquid chromatography, as well as the cell cycle inhibitory and apoptotic effects of Pa being investigated in U87MG glioblastoma cells. The Pa exhibited strong anticancer effects in the absence of direct photo-irradiation against various cancer cell lines, including U87MG, SK-OV-3, and HeLa cells. Among the cancer cells, the strongest anticancer activity of Pa exhibited on U87MG cells with IC50 values of 2.8 mu g/ml. In addition, Pa specifically had cytostatic activity on glioblastoma cells rather than human umbilical vein endothelial cells. Analysis of the cell cycle distribution showed that Pa induced G0/G1 arrest of U87 MG cells. In addition, arrested cells induced late apoptosis and DNA degradation under dark condition. These results suggest that Pa isolated from G. elliptica is a potential glioblastoma-specific anticancer agent without side effects on normal cells.
Keywords: PHOTODYNAMIC THERAPY; IN-VITRO; SELECTIVE CYTOTOXICITY; SCUTELLARIA-BARBATA; ENHANCES APOPTOSIS; CANCER; TUMOR; VIVO; CELLS; PHOTOSENSITIZER